Development of selective CBP/P300 benzoxazepine bromodomain inhibitors - Popp, T; Tallant, C; Rogers, C; Fedorov, O; Brennan, P; Müller, S; Knapp, S; Bracher, F (American Chemical Society, 2016)
CBP (CREB (cAMP responsive element binding protein) binding protein (CREBBP)) and P300 (adenovirus E1A-associated 300 kDa protein) are two closely related histone acetyltransferases (HATs) that play a key role in the regulation of gene transcription. Both proteins contain a bromodomain flanking the HAT catalytic domain that is important for the targeting of CBP/P300 to chromatin and which offeres an opportunity for the development of protein-protein interaction inhibitors. Here we present the development of CBP/P300 bromodomain inhibitors with 2,3,4,5-tetrahydro-1,4-benzoxazepine backbone, an N-acetyl-lysine mimetic scaffold that led to the recent development of the chemical probe I-CBP112. We present comprehensive SAR of this inhibitor class as well as demonstration of cellular on target activity of the most potent and selective inhibitor TPOP146, which showed 134 nM affinity for CBP with excellent selectivity over other bromodomains.